Fit for work? Redefining 'Normal' and 'Extreme' through human enhancement technologies. (July 2015) - Bloomfield, Brian; Dale, Karen
This article focuses on how the categories of 'normal' and 'extreme' in the context of work might be renegotiated through the development of human enhancement technologies which aim to enable the human body to be pushed beyond its biological limits. The ethical dimensions of human enhancement technologies have been widely considered, but there has been little debate about their role in the broader world of employment—nor, conversely, the recognition that prevailing employment relationships might shape the development and uptake of such technologies. Addressing the organisation of work within 'advanced' capitalist economies, this article considers the arguments for the potential use of cognitive enhancers, so-called 'smart drugs', in various domains of work such as surgery and transportation. We argue that the development of human enhancement technologies might foster the normalisation of 'working extremely'—enabling longer working hours, greater effort or increased concentration—and yet at the same time promote the conditions of possibility under which workers are able to work on themselves so as to go beyond the norm, becoming 'extreme workers'. Looking at human enhancement technologies not only enables us to see how they might facilitate ever greater possibilities for working extremely but also helps us to understand the conditions under which cultures of extreme work become the norm and how workers them/ourselves accept or even embrace such work.